Myelography with iohexol (Omnipaque): review of 300 cases. - Burrows, E H (American Journal of Neuroradiology, 1985)
The side effects of iohexol were evaluated in the 300 patients who had nonemergency myelography over a 9 month period. No patients studied with myelography were excluded from the iohexol trial. Age range was 14-86 years. Introduction was by lumbar puncture in 206 patients and by lateral C1-C2 injection in 94. Side effects, including discomfort, were denied by 81.3% of the patients. The other 18.7% had adverse reactions, the most common being headache, reported by 11% of the total population studied. Image quality was judged unsatisfactory in 8.1% of cervical myelograms and in 2.6% of lumbar myelograms. With lumbar injection, cervical myelograms were judged to be inadequate in 13.5%; with cervical injection, lumbar myelograms were inadequate in 25%. Iohexol caused significantly fewer side effects in the 300 patients than would have been expected with metrizamide. The low cost and ease of use are additional factors that favor iohexol as the contrast agent of choice for myelography.